Persons and Their Minds Towards an Integrative Theory of the Mediated Mind - Brinkmann, Svend (Taylor & Francis, 2017)
Today's approaches to the study of the human mind are divided into seemingly opposed camps. On one side we find the neurosciences, with their more or less reductionist research programs, and on the other side we find the cultural and discursive approaches, with their frequent neglect of the material sides of human life. Persons and their Minds seeks to develop an integrative theory of the mind with room for both brain and culture. Brinkmann's remarkable and thought-provoking work is one of the first books to integrate brain research with phenomenology, social practice studies and actor-network theory, all of which are held together by the concept of the person.